Franny, the queen of Provincetown - Preston, John (Little sister's classics, 2005)
First published to wide acclaim in 1983, Franny was a book of gay heroism and camaraderie in the shadow of the burgeoning AIDS crisis. Today, one can read it with a sense of nostalgia, and with the knowledge that Franny's dream of a society that accepts gays and lesbians without question is closer to fruition, but far from complete.